Methodological advances in research on social movements, conflict, and change - Maher, Thomas V.; Schoon, Eric W. (Emerald Publishing Limited, 2023)
The 21st century has brought many changes to peacebuilding, armed conflicts, and social movements. Organizations and scholars alike have developed new techniques for bridging cultural divides and enhancing democracy and respect for human rights. Moreover, technological changes have significantly altered conflict spaces. Methodological Advances in Research on Social Movements, Conflict, and Change explores methods for studying contentious politics in the context of these broader social changes. Contributors advance methodological scholarship by developing new tools, discussing new sources of data and their relative value, and addressing controversies and ethical issues that have emerged in the process of collecting or analyzing data. Acknowledging how more movements are using a wider range of tactics to influence a rapidly changing, deeply interconnected world, Methodological Advances in Research on Social Movements, Conflict, and Change appeals to scholars interested in how the study of social movements, peace, and conflict has developed and adapted to keep pace with ongoing socio-political and technological change.
Keywords: Social movements -- Research -- Methodology.; Social conflict -- Research -- Methodology.; Social change -- Research -- Methodology.; Social Science -- Research.; Social research & statistics.; elektronické knihy; electronic books